TRANSITION TO NUCLEAR WAR: INDONESIAN PERSPECTIVE RESPONSE USING ANALYTICAL HIERARCHY PROCESS AND STRENGTHS, WEAKNESSES, OPPORTUNITIES AND THREATS METHOD - Anang Puji Armanto; Benny Octaviar; Muchammad Bachtiar; Prabaswari Prabaswari; Purnomo Yusgiantoro; I Wayan Midhio (The Republic of Indonesia Defense University, 2022)
Since the end of World War II, the use of nuclear power as a weapon of war has been criticized for causing the deaths of up to 55 million people. Then there was a shift in the use of nuclear power from military to peaceful purposes, such as economic goals, and many countries built nuclear reactors as an alternative to conventional fuels. In addition, nuclear power can also serve as a very strong deterrent factor to prevent open war. Indonesia's geographical position is currently surrounded by countries that own nuclear reactors, such as North Korea, Iran, Russia, China, and India, followed by the formation of the AUKUS alliance of Australia, the United Kingdom (U.K.), and the United States (U.S.). With the geopolitical conditions and escalation in the region, Indonesia should take precautionary measures to avoid a nuclear war in the region. This study aims to identify the best anticipatory steps that can be taken by conducting in-depth Focus Group Discussions (FGD) and extracting data using questionnaires from ten academics, diplomats, nuclear experts, military personnel, and professionals, which results in several alternative options. The option is then analyzed to identify which is the best by using Analytical Hierarchy Process (AHP) method and confirmed with Strengths, Weaknesses, Opportunities, and Threats (SWOT ) Analysis. Based on the findings of the analysis, the sequence of anticipatory steps that must be taken is as follows: 1) through diplomacy; 2) through the strengthening of defense equipment; 3) participation in certain alliances, either temporarily or permanently, and 4) building a national nuclear capability as a deterrent. As a result, diplomacy remains the primary option for resolving the region's escalation